Optimisation of Cross-Border Project Management In Higher Education Institutions in the Context of the Impact of Global Economic Crises - Olha Hryhoriv; Liliia Mykhailyshyn; Viktoriia Marusiak (Vasyl Stefanyk Precarpathian National University, 2023)
In today's globalized and interconnected world, the impact of global crises poses increasing risks to the economic situation of each country in particular. The study of cross-border cooperation in the context of current crisis processes allows us to identify new risks and ways to minimize them. The purpose of the study is to analyze ways to optimize the management of cross-border projects in the context of the impact of global economic crises. Scenario planning, SWOT analysis, statistical and mathematical research methods are used in the course of the study. The article discusses the peculiarities of managing cross-border projects on the example of the Precarpathian National University in the context of the impact of global economic crises. Using the example of the university, the author analyzes the implementation of cross-border projects for the period of 2020-2022, which occurred during two crises. The first global economic crisis is caused by the COVID-19 pandemic and the second regional crisis is caused by the war in Ukraine. The risks faced by the grantee in implementing international programs are identified. The study analyzed four different cross-border projects, which made it possible to assess all the risks in more detail and identify existing problems. For a detailed analysis, the medium-sized PrePOD project was selected, which operated from 2020 to 2022 and received an average amount of funding. The strengths and weaknesses of cross-border cooperation were assessed. The study pays special attention to the role of the Precarpathian National University, emphasizing the need for financial risk management, effective communication, compliance with the law, and adaptation of national legislation to European standards. The paper formulates strategies for improving the management of cross-border projects in the context of global crises, and proposes to create research centers to improve the management of grant activities. It has been determined that flexibility and communication are the international factors that can reduce the impact of crisis processes on the implementation of international cooperation.